Four unusual sinonasal and sinorbital lesions: a case series - Ullal, Aishwarya; Ajith, Arun P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Presentations of Sino nasal lesions may be indistinguishable and therefore represent diagnostic and therapeutic dilemma due similarities of non-neoplastic and neoplastic lesions at initial presentation may lead to a significant delay in the diagnosis. This case series has been reported to through light on four different case scenarios that presented to us, their diagnosis and management. This was a case series of four unusual cases of the sinonasal and sinoorbital region that presented with symptoms of nasal obstruction, rhinnorhea, epistaxis, radiological and diagnostic nasal endoscopy was performed. Using functional endoscopic sinus surgery and lynch Howarth method the lesions were excised. As sino nasal and sinoorbital lesions present with similar clinical features accurate diagnostic procedures such as nasal endoscopy and radiological investigations, histopathological investigations play an important role in the management of the lesions.